Impact of COVID‐19 on rural and remote student placements in Australia: A national study. (1st February 2022) - Hoang, Ha; Jessup, Belinda; Obamiro, Kehinde; Bourke, Lisa; Hellwege, Barbara; Podubinski, Tegan; Heaney, Susan; Sheepway, Lyndal; Farthing, Annie; Rasiah, Rohan; Fitzroy, Robyn; Jatrana, Santosh; et al.
Abstract: Objective: To investigate students' perceptions of the impact of coronavirus SARS‐CoV‐2 on rural and remote placements facilitated by 16 University Departments of Rural Health in Australia in 2020. Design: A mixed‐method design comprising an online survey and semi‐structured interviews. Setting: Australia. Participants: Allied health, nursing and medical students with a planned University Departments of Rural Health‐facilitated rural or remote placement between February and October 2020. Intervention: A planned rural or remote placement in 2020 facilitated by a University Departments of Rural Health, regardless of placement outcome. Main outcome measures: Questionnaire included placement outcome (completed or not), discipline of study (nursing, allied health, medicine), and Likert measures of impact to placement (including supervision, placement tasks, location, accommodation, client contact and student learning) and placement experience (overall, support, supervision, university support). Semi‐structured interviews asked about placement planning, outcome, decisions, experience and student perceptions. Results: While coronavirus SARS‐CoV‐2 reportedly impacted on the majority of planned placements, most students (80%) were able to complete their University Departments of Rural Health‐facilitated placement in some form and were satisfied with their placement experience. Common placement changes included changes to tasks, setting, supervisors and location. Allied health students were significantly more likely to indicate that their placement had been impacted and also felt more supported by supervisors and universities than nursing students. Interview participants expressed concerns regarding the potential impact of cancelled and adapted placements on graduation and future employment. Conclusions: The coronavirus SARS‐CoV‐2 pandemic was reported to impact the majority of University Departments of Rural Health‐facilitated rural and remote placements in 2020. Fortunately, most students were able to continue to undertake a rural or remote placement in some form and were largely satisfied with their placement experience. Students were concerned about their lack of clinical learning and graduating on time with adequate clinical competence.